COURAGEOUS CONVERSATIONS IN CHILD AND YOUTH CARE: NOTHING LOST IN THE TELLING - Jin-Sun Yoon (International Journal of Child, Youth and Family Studies, 2012)
Following the tradition of Indigenous and Korean elders with whom I have had the great privilege to work and learn from, I would like to start by sharing my gratitude for the land that we are on. In this way, we ground ourselves spiritually, emotionally, and physically by acknowledging the presence of our ancestors (current and past) in everything we do. I am a child immigrant from South Korea so I want to acknowledge that this is not the Indigenous land of my ancestors. I would like to point out the privilege of being a visitor who can work, play, and raise my family on unceded traditional Coast and Strait Salish territories. Back in the early 1990s, the First Nations House of Learning was opened while I was a graduate student at the University of British Columbia. At that time, I understood that it was important to acknowledge traditional territories. What I used to believe was basic protocol in the presence of Indigenous people and during ceremonies has now been transformed to an embodied way of living that guides me in my daily practice.